Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/mc.23121
|View full text |Cite
|
Sign up to set email alerts
|

XRCC1‐mediated DNA repair is associated with progression‐free survival of multiple myeloma patients after autologous stem cell transplant

Abstract: Autologous stem cell transplant (ASCT) with high‐dose melphalan (HDM) is the standard treatment for fit multiple myeloma (MM) patients. It is generally believed that some DNA repair proteins impact the activity to repair melphalan‐induced DNA damage, thus potentially contributing to the patient's clinical response. However, knowledge of these proteins is limited. In the current study, we investigated the roles of XRCC1, a protein involved in base excision repair and single‐strand break repair, in melphalan res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…SCC83-82, a precancerous oral cell line, was kindly provided by Dr. Christopher Weghorst at the College of Public Health, The Ohio State University (31). Cells were grown in advanced DMEM/F12 (Life Technologies Corporate), supplemented with 5% FBS, and 1×Antibiotic Antimycotic solution as previously described (32).…”
Section: Methodsmentioning
confidence: 99%
“…SCC83-82, a precancerous oral cell line, was kindly provided by Dr. Christopher Weghorst at the College of Public Health, The Ohio State University (31). Cells were grown in advanced DMEM/F12 (Life Technologies Corporate), supplemented with 5% FBS, and 1×Antibiotic Antimycotic solution as previously described (32).…”
Section: Methodsmentioning
confidence: 99%
“…Assays were performed in triplicate at least twice. Absolute IC 50 values (the concentration of cisplatin required to inhibit 50% of the cell viability) were determined using Kaleidagraph software (Synergy Software, Reading, PA, USA) as previously described (26).…”
Section: Methodsmentioning
confidence: 99%
“…Contraindicatory data from different studies have shown that genetic variants have been associated with the response of MM patients to high dose melphalan- based chemotherapy via single nucleotide polymorphisms (SNPs) in genes of the BER pathway [ 26 , 27 ]. Among these genes, XRCC1, a protein involved in BER and single-strand break repair, significantly resulted in the increase of accumulation of melphalan-induced DNA damage lesions in XRCC-1 –deficient myeloma cells and, in turn, sensitized them to melphalan treatment [ 28 ].…”
Section: Hdacs In Different Ddr Mechanismsmentioning
confidence: 99%